2022
DOI: 10.3389/fpsyg.2022.948081
|View full text |Cite
|
Sign up to set email alerts
|

The Attention Training Technique Reduces Anxiety and Depression in Patients With Coronary Heart Disease: A Pilot Feasibility Study

Abstract: Background and ObjectivesDepression and anxiety symptoms are highly prevalent in coronary heart disease (CHD) patients and associated with poor outcome. Most psychological treatments have shown limited effectiveness on anxiety and depression in these patients. This study evaluates the feasibility of the attention training technique (ATT) in CHD patients with symptoms of anxiety and/or depression.MethodsFive consecutive CHD patients with significant depression and anxiety symptoms with Hospital Anxiety and Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…This is interesting because Type D personality has been highly correlated with neuroticism ( De Fruyt and Denollet, 2002 ). Together with our results, suggesting a potential overlap between depression, anxiety and NA, further studies on the treatment for depression and anxiety in patients with CAD may also assess the effectiveness on NA and SI as well as Type D. Recently, the attention training technique—a component of metacognitive therapy—showed effect on anxiety, depression and NA in these patients ( Dammen et al, 2022 ). Whether the attention training technique also influences the presence of Type D as well as the risk for recurrent adverse events in CAD patients remains to be investigated.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is interesting because Type D personality has been highly correlated with neuroticism ( De Fruyt and Denollet, 2002 ). Together with our results, suggesting a potential overlap between depression, anxiety and NA, further studies on the treatment for depression and anxiety in patients with CAD may also assess the effectiveness on NA and SI as well as Type D. Recently, the attention training technique—a component of metacognitive therapy—showed effect on anxiety, depression and NA in these patients ( Dammen et al, 2022 ). Whether the attention training technique also influences the presence of Type D as well as the risk for recurrent adverse events in CAD patients remains to be investigated.…”
Section: Discussionsupporting
confidence: 72%
“…This may be due to the NA construct overlapping with depression and anxiety or an underlying dimension between depression, anxiety and NA. A recent study indicated that there may be such an underlying dimension, particularly between HADS-D and NA (Tunheim et al, 2022). Moreover, Type D personality may render the person vulnerable to experiencing higher levels of anxiety and depression, which may be a consequence to being diagnosed with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of MCT results from the confluence of learning and practice together, suggesting that practice must be adequate and regular. Dammen et al ( 51 ) demonstrated that ATT exercise, which is also a part of our web app in particular leads to significant improvement in anxiety and depression symptoms. The exercise area was introduced in a module in the middle of the training program where the participants were instructed to practice regularly.…”
Section: Discussionmentioning
confidence: 97%
“…This makes it particularly well suited to CHD patients who often present with mixed anxiety and depression. Finally, in a recent open study, we found ATT delivered face-to-face in a 6- session group format to be feasible and potentially effective for improving depression and anxiety symptoms in CHD patients ( Dammen et al, 2022 ), which holds considerable appeal for use in increasingly busy cardiac follow-up clinics. The next progressive step is to test the effectiveness of ATT in a randomized controlled clinical trial.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, RCTs have reported ATT delivered in group formats to be effective in reducing symptoms of anxiety and depression among a student population ( Haukaas et al, 2018 ). There is also preliminary evidence from an open study that ATT is feasible and potentially effective in treating symptoms of anxiety and depression in CHD patients ( Dammen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%